Evaluación del crecimiento “In vitro” de Trichoderma spp. en dos medios de cultivo y su antagonismo frente a los hongos fitopatógenos Fusarium spp., Sclerotinia spp., y Rhizopus spp. - Fajardo Navarrete, Piero C (2008)
In order to evaluate the potential of the fungus Trichoderma spp. as a biological control agent of various phytopathogens affecting to different cultivation during all cycle of evolution. two assays were carried out in the year 2006. The first assay was evaluated the speed of rise of Trichoderma spp., in two "culture medias": 1) Pope Agar Dextrosa (PDA); and other, 2) Agar Extract of Malta (AEM). The work procedure in this first phase of study was established using 8 'strains" of Trichoderma spp., insulate in three area of production in the superior farming and Livestock Polytechnic School of Manabi (ESPAM) "Manuel Felix Lopez" ("MFL") located in Calceta-Manabi, with the following code identification: TACv1 = Trichoderma spp. Area of conventional production # 1. TACv2 = Trichoderma spp. Area of conventional production # 2. TAC1 = Trichoderma spp. Area of the cacao # 1. TAC2 = Trichoderma spp. Area of the cacao # 2. TAC3 = Trichoderma spp. Area of the cacao # 3. TAC4 = Trichoderma spp. Area of the cacao # 4. TAE1 = Trichoderma spp. Area of ecological production # 1. TAE1 = Trichoderma spp. Area of ecological production # 2. The experimental design used in this bioassay was a complete aleatory (DCA) with three replications. Two factors were studied. "strains' of (Factor A) and "culture medias" (Factor B). The best results were obtained in the strains: TAC1, TAE1, TAC2 and the culture media codified as: PDA. Which were used subsequently in the bioassay 2. Where was evaluated the antagonist capacity of selected strains in bioassay # 1 in from of the phytopathogens Fusarium spp., Sclerotinia spp. and Rhizopus spp. It was established a randomized block design with a complete aleatory (DCA): which four replications. Here it was confirmed in vitro" that the Thichoderma spp.. holds the control of 100% up the three pathogens in the fifth day of evaluate stady. In conclusion, the strains TAC1, TAE1 and TAC2 producing a good biological control "in vitro" of the phytopathogens used in this study; however, the strains codified as:TAC2 showed the best characteristic to be multiplied and liberated in the field, because a the higher sporulations observed during its development. This last characteristic is fundamental to fast establish in the field. While the strains TAC1 and TAE1 showed a poor sporulation although it's good development.